Spectrophotometry determination of nitrate in soil extracts without chemical reduction - Miyazawa, Mario; Pavan, Marcos Antonio; Block, Maria de Fátima M. (Pesquisa Agropecuaria Brasileira, 2014)
The use of two wavelenghts for assessing NO-3 in acid soil extracts by ultraviolet spectrophotometry were avaluated. The procedure consisted in measuring the absorbance of the soil extract at 210 nm without chemical reduction (NO-3 + interfering ions) and at longer wavelength (λ) where the ultraviolet light absorption due to NO-3 is neglegible and that due to interfering ions is similar to that measured at 210 nm, in which the NO-3 had been chemically reduced to NH+4. This technique was evaluated for a selection of acid and well aerated oxisols of Paraná (Brazil) agricultural region. The results showed that once "λ" value is determined for that soil it can be used repetitively for the same soil unit. The nitrate content in acid and well aerated oxisols were essentially identical for the chemical reduction at 210 nm and two-wavelenght methods. The use of two-wavelength ultraviolet spectrophotometry without chemical reduction is suggested as an additional method for assessing NO-3 in acid soil extracts because of its rapidity, simplicity and precision.